Assessing Learning Skills and Work Habits: What Do Report Card Data Tell Us? - Merchant, Stefan Denis; Klinger, Don; Kirby, John (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
Many school systems ask teachers to assess and report upon aspects of student performance beyond academic achievement. In Ontario, K–12 teachers assess a common set of six Learning Skills and Work Habits. How well teachers are able to undertake these assessments is not well studied. This study examines Grade 9 and 12 report card data from two districts in Ontario, Canada to determine to what extent different learning skills are assessed independently of each other, and to what extent they are associated with teacher-awarded academic achievement and achievement on a standardized Grade 9 mathematics examination delivered by Ontario’s Educational Quality and Accountability Office (EQAO). Results indicate that the set of six Learning Skills and Work Habits are assessed as a unitary construct. Grades on these skills have higher correlations with teacher-awarded grades than with standardized test scores. Finally, gender differences in both academic achievement and achievement on the set of skills are investigated.